Biochemical and Biomechanical Properties of the Rabbit Nasal Septum. (23rd August 2013) - Watson, Jeffrey; Gruissem, Sophia; Yamaguchi, Tomonori; Briggs, Kris; Sah, Robert; Masuda, Koichi; Watson, Deborah
Abstract : Objectives: 1) Characterize biochemical and biomechanical properties of New Zealand White rabbit septal cartilage for future utilization in rabbit septal cartilage tissue engineering studies. 2) Determine whether tensile and bending properties vary when measured in different axes. Methods: Nasal septa were harvested from adult New Zealand White rabbits post‐mortem. Confined compression testing was performed. Samples cut in the vertical and anterior‐posterior (AP) plane were subjected to tensile testing and 3‐point bending. Biochemical assays determined the Glycosaminoglycans (GAG), total collagen, and DNA concentrations in each sample. Results: Confined compression demonstrated an average compressive modulus (HAO) of 0.82 (±0.23 MPa). In tensile testing, peak stress of samples cut in the vertical plane (6.61±1.28 MPa) were significantly greater (p=0.02) than in the AP plane (5.22±1.31 MPa). Tensile stiffness at failure strain for vertical (22.90±5.51 MPa) and AP (18.67±9.56 MPa) samples did not differ significantly (p > 0.05). The flexural moduli of samples cut in the vertical plane (39.31±16.6 MPa) and AP plane (39.32±20.24 MPa) were also not significantly different (p > 0.05). Biochemical characterization demonstrated an average concentration of 43.81±8.34 µg GAG, 104.71±21.52 µg total collagen, and 0.23±0.05 µg DNA per mg wet weight. Conclusions: Rabbit septal cartilage is anisotropic; tensile strength was higher in the vertical plane than in the AP plane. Compared with published properties of human septal cartilage, rabbit septal cartilage is mechanically stronger, stiffer, and less flexible. Rabbit septal cartilage has a similar DNA content, with higher GAG and total collagen levels than values published for human septal cartilage.